Cutaneous Allodynia is already present in young adults with headache - Sousa, Cirlane de Maria da Silva (2024)
Introduction: Cutaneous Allodynia (CA) is a painful response to a non-nociceptive stimulus, which is considered a marker of central sensitization. Objective: To evaluate the frequency of CA in individuals with and without headache. Materials and Methods: Volunteers of both sexes, aged 18 to 30 years, with and without headache participated. Those with abuse of analgesics and anesthetic block in the last three months were excluded. A questionnaire with general data prepared by the author himself, the Headache Screening Questionnaire (HSQ) for headache diagnosis and the 12 item Allodynia were applied. Symptom Checklist/Brazil (ASC-12/Brazil) to assess the severity of CA. Quantitative variables were described by mean and standard deviation and qualitative variables were presented in frequency. Results: 60 individuals were evaluated, with n=30 in the headache group, with a mean age, weight and height of 23.06±4.97 years, 62.02±13.09 kg and 1.62±0.05 m 2, respectively, where n=19 (64%) with migraine and n=11 (36%) with tension-type headache (TTH); n=30 in the control group with a mean age, weight and height of 22.03±0.09 years, 58.55±11.85 kg and 1.63±3.09, respectively. A higher frequency of CA was observed in the headache group compared to the control group n=28 (93.33%) and n=7 (26%), respectively, with the most frequent severity in the headache and control groups being mild and moderate, respectively, greater severity was also observed in those with migraine compared to those with TTH. Conclusion: Young adult individuals with headache have a higher frequency and severity of CA compared to individuals without headache.